2020
DOI: 10.20870/ijvr.2020.20.2.3151
|View full text |Cite
|
Sign up to set email alerts
|

Children's memory of a story experienced with virtual reality versus traditional media technology

Abstract: Immersive Virtual Reality Technology (IVR) is a visual multi-sensory computer-simulated environment that perceptually surrounds an individual, creating the illusion that one has “stepped inside” and is included in, and interacting with the generated world. Although IVR has been suggested as a tool to enhance learning, existing work has not examined how IVR presentations, compared with other types of storytelling, facilitate or interfere with children’s memory formation. Here, we present data from a study of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Recent studies conducted within the same framework have demonstrated a positive effect of IVR and interactivity on enjoyment, interest, self-efficacy, expected outcomes, perceived embodiment, spatial presence, motivation and behavioral intention changes compared to the same content presented using 2D desktop or conventional multimedia technologies, and have done so in very different fields and subject areas ( Ahn et al, 2022 ; Andersen et al, 2022 ; Makransky and Klingenberg, 2022 ; Makransky and Mayer, 2022 ; Petersen et al, 2022 ; Vandeweerdt et al, 2022 ; Plechatà et al, 2022a , b ; Bagher et al, 2023 ; Stenberdt and Makransky, 2023 ). A similar pattern of results was found with young children asked to perform tasks such as remembering and recalling a story and the related emotions ( Araiza-Alba et al, 2020a ), understanding and recalling seaside safety instructions ( Araiza-Alba et al, 2021b ) and problem solving ( Araiza-Alba et al, 2021a ).…”
Section: Introduction and Goalsupporting
confidence: 76%
See 1 more Smart Citation
“…Recent studies conducted within the same framework have demonstrated a positive effect of IVR and interactivity on enjoyment, interest, self-efficacy, expected outcomes, perceived embodiment, spatial presence, motivation and behavioral intention changes compared to the same content presented using 2D desktop or conventional multimedia technologies, and have done so in very different fields and subject areas ( Ahn et al, 2022 ; Andersen et al, 2022 ; Makransky and Klingenberg, 2022 ; Makransky and Mayer, 2022 ; Petersen et al, 2022 ; Vandeweerdt et al, 2022 ; Plechatà et al, 2022a , b ; Bagher et al, 2023 ; Stenberdt and Makransky, 2023 ). A similar pattern of results was found with young children asked to perform tasks such as remembering and recalling a story and the related emotions ( Araiza-Alba et al, 2020a ), understanding and recalling seaside safety instructions ( Araiza-Alba et al, 2021b ) and problem solving ( Araiza-Alba et al, 2021a ).…”
Section: Introduction and Goalsupporting
confidence: 76%
“…In their own meta-analysis, Coban et al (2022) , considered fourteen previous meta-analyses and 105 independent ESs (Effect Sizes) from 48 primary studies: They found an overall ES of g = 0.38, which corresponds to a small to medium positive effect. Araiza-Alba et al (2020a , b) arrived at a similar conclusion concerning the use of desktop VR and IVR with children.…”
Section: Introduction and Goalmentioning
confidence: 56%
“…The sensation of presence and immersion are frequently connected with higher levels of involvement and more intense emotions and aspects that are associated with improved learning outcomes. Hence, the higher the sense of presence and emotional involvement during the experience, the easier the children will recall the content presented to them (Araiza-Alba et al, 2020). In terms of children with special needs, as well as those who are visually impaired, autistic, have social anxieties or have mental health issues, VR brings possibilities for socializing, exploration, adventure, and experiences that they would not have in the actual world.…”
Section: Benefits Of Applying Vr Technology To Children Museumsmentioning
confidence: 99%
“…Apart from entertainment purposes, such video material has been used within a wide variety of topics, such as sports, news coverage, and, of course, education (for detailed examples, please see Araiza‐Alba et al, 2020; Barreda‐Ángeles et al, 2021; Ivars‐Nicolás et al, 2020; Shafi et al, 2020). Particularly for this purpose, such videos provide several benefits (Violante et al, 2019), including the potential to take on others' perspectives, experience otherwise inaccessible situations, or perceive a sense of freedom by choosing an individual vantage point.…”
Section: Introductionmentioning
confidence: 99%